PENGEMBANGAN MANAJEMEN TEKNOLOGI PADA PERUSAHAAN JASA FLIGHT CATERING PT AEROFOOD (ACS) DENPASAR - , Cokorda Anom Bayu Sadyasmara; , Dr. Ir. Makhmudun Ainuri, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The unique characteristics of flight catering services company and it high complexity, requiring a method or approach to ensure each operational processes run in accordance with the initial goal that has been set. Technology management can be used as a solution, because by utilize the added value and the right innovation of technology will produce a powerful weapon for industrialization, increase the productivity, support of growth and improve the standard of live. Assessment of technology management implementation was then performed to determine the position and the utilization of technology in the company, which technology used in its function as a transformer that converting all input to output within a process of transformation. The technology consists of four interrelated components, namely technoware, humanware, infoware and orgaware. The Technometric method which was formulated by UNESCAP (1989) with company adjustment used to determine their content of technology with a focus on the four components of technology. Based on the results of the assessment, the company has a technological contribution value of 0.57 of the maximum value 1, wherein the very influential are component of humanware (decisiveness, the impact and influence, level of education) and orgaware (operational development and the mechanism of incentive system).